Effects of hydrogen addition on soot emission of methane and propane coaxial jet diffusion flames - Kazuhiro YAMAMOTO; Wataru KIMURA (Journal of Thermal Science and Technology, 2024)
In recent years, environmental problems such as global warming and air pollution have been recognized more seriously. Soot in the combustion products is one of the causes of air pollution. Hydrogen is now attracting attention as an alternative fuel to fossil fuels because it can be carbon-neutral fuel synthesized from renewable energy sources. If hydrogen is mixed with hydrocarbon fuels, it is possible to reduce CO2 emission. In this study, we investigated the effect of hydrogen addition on a coaxial jet diffusion flame. We used methane and propane as main fuels, and soot region was visualized using a laser induced incandescence (LII) method. In experiments, two-dimensional distribution of the soot concentration was obtained, and the maximum soot volume fraction and the total soot volume were evaluated from the LII signal. In order to clarify the effect of hydrogen addition, nitrogen was also added to the main fuel, and both results were compared.